Hubungan Tingkat Pendidikan Dan Sikap Ibu Hamil Dengan Kunjungan Antenatal Care Di Puskesmas Kabaena Barat - Devi, Resky (LPPM - STIKES Pemkab Jombang, 2025)
In Indonesia, the suboptimal use of antenatal services is also influenced by the same factors as before, namely age, knowledge, information media, family support, work, pregnancy factors, health service providers, skilled personnel and adequate facilities. Lack of knowledge and passive maternal attitudes greatly impact the mother's understanding of ANC examinations. The type of research is descriptive research, namely describing data as research results, using a cross-sectional design. The population in this study was 35. The sampling technique was Accidental Sampling, the sampling formula used the Slovin formula. The sample in this study was 30 samples. Data analysis used the Chi-Square test. The research instrument used a questionnaire. The results of the study based on the Chi-Square statistical test on the variable of education level with Antenatal Care visits obtained p-value = 0.041 where p-value <? (0.041 <0.05) and the Chi-Square statistical test on the variable of attitude with Antenatal Care visits obtained p-value = 0.292 where p-value <? (0.292 > 0.05) The conclusion of this study is that there is a relationship between education level and Antenatal Care visits and there is no relationship between attitudes and antenatal care visits in pregnant women at the West Kabena Health Center.